Soluble Membrane Attack Complex: Biochemistry and Immunobiology - Barnum, Scott R.; Bubeck, Doryen; Schein, Theresa N. (Frontiers in Immunology, 2020)
The soluble membrane attack complex (sMAC, a.k.a., sC5b-9 or TCC) is generated on activation of complement and contains the complement proteins C5b, C6, C7, C8, C9 together with the regulatory proteins clusterin and/or vitronectin. sMAC is a member of the MACPF/cholesterol-dependent-cytolysin superfamily of pore-forming molecules that insert into lipid bilayers and disrupt cellular integrity and function. sMAC is a unique complement activation macromolecule as it is comprised of several different subunits. To date no complement-mediated function has been identified for sMAC. sMAC is present in blood and other body fluids under homeostatic conditions and there is abundant evidence documenting changes in sMAC levels during infection, autoimmune disease and trauma. Despite decades of scientific interest in sMAC, the mechanisms regulating its formation in healthy individuals and its biological functions in both health and disease remain poorly understood. Here we review the structural differences between sMAC and its membrane counterpart, MAC, and examine sMAC immunobiology with respect to its presence in body fluids in health and disease. Finally, we discuss the diagnostic potential of sMAC for diagnostic and prognostic applications and potential utility as a companion diagnostic.